Determination of External Auditor Selection - Septiana, Milla; Khafid, Muhammad (Accounting Analysis Journal, 2019)
This study aims to examine the effects of the size of independent commissaries, the effectiveness of audit committee and leverage on the selection of external auditors with firm size as moderation variable. The population of this research was all the companies of financial sector listed on the Indonesia Stock Exchange at 2017 as many as 95 companies. The samples were determined using purposive sampling technique. There were 89 companies as research samples and units of analysis. Moreover, the data were collected by documentation method. Analysis of research data used descriptive statistics and inferential statistics. The results indicate that the size of independent commissaries, the effectiveness of audit committee and leverage significantly have positive effect on the auditor selection. Firm size moderates the effects of the size of board of independent commissaries and leverage on the auditor selection, but does not moderates the effect of audit committee effectiveness on the auditor selection. Based on the research results, it shows that the size of board of independent commissaries with firm size as moderation can increase the selection of Big Four external auditor, while leverage with firm size as moderation can decrease the selection of Big Four external auditor.